2022-RA-1375-ESGO Minimally invasive vs. open interval debulking surgery in advanced ovarian cancer patients: pattern of recurrence and oncological outcome in a propensity matched population. (20th October 2022) - Conte, Carmine; Rosati, Andrea; Marchetti, Claudia; Aterno, Donatella; Alletti, Salvatore Gueli; Scambia, Giovanni; Fagotti, Anna
Abstract : Introduction/Background: Minimally invasive interval debulking surgery (MI-IDS) is a promising approach for women with optimal response to neo-adjuvant chemotherapy (NACT). Safety is currently under investigation with a prospective randomized multicentric international phase III trial. This study aims to compare sites and spread of recurrence and overall survival (OS) after MI-IDS or laparotomic IDS (LPT-IDS). Methodology: We retrospectively identified all epithelial advanced ovarian cancer patients who underwent IDS after NACT between 2014 and 2020. Patients were divided in two groups according to the type of approach at IDS: MIS or laparotomic. The choice for one approach vs the other was surgeon dependent. A 1:1 propensity score-matched analysis was applied to balance the two surgical groups according to prognostic clinical factors such as radiological response after NACT, Ca125 serological response, number of peritoneal sites involved, and high-volume surgeon (≥30 cytoreductive surgeries per year). The site of recurrence was classified based on PET/CT scan, as peritoneal, lymph-nodal, or other (parenchymal and mixed). The extension of recurrence was classified as single, oligometastatic(≤3 nodules), multifocal/diffused (>3 nodules or wide peritoneal spread). Results: In the propensity-matched population, 92 patients underwent MI-IDS and 92 LPT-IDS. We documented 138 recurrences (75.8%) without statistically significant differences between the two populations (72.2% vs. 79.3%;p=0.171) ( table 1 ). Information on the site of recurrence was available in 117 of 138 patients, and we reported a high rate of mixed disease in both groups (59.3% vs. 58.7%) with a low rate of lymph-nodal recurrence (14.8% vs. 11.1%)(p=0.780). Most patients relapsed as a widespread disease without difference between the two approaches (74.1% vs. 80.6%; p=0.560).The median OS was 43 months in MI-IDS and 48 months in LPT group(p=0.968). Conclusion: This study shows no significant impact of the type of surgical approach at IDS (MIS vs. LPT) on the site and extension of recurrence and overall survival.